Evaluation of digital terrain model (DTM) derived from non-metric camera and DVP geomatic system software - 213970 Norfariza Zainal (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2005